PERAN SOSIAL DALAM PELAKSANAAN PENDIDIKAN AKHLAK - Rahmadika, Sarah (TARBAWY : Indonesian Journal of Islamic Education, 2021)
Abstract. The social community is very influential in the success of education in schools. Both are interrelated and cannot be separated from each other. The sociological contribution discussed here is about the role of the family, community and school in achieving the intended educational outcomes for students, namely students who have good character and excel in their schools. Moral education itself becomes the foundation for the formation of a good society. For this reason, it is necessary to know what patterns of interaction which can exist between the three parties and what are the roles of families and communities in educating students’ morals. This research is qualitative in nature, the data collection techniques are carried out with literature studies and objects of the study is the implementation of moral education in schools and sociology which are tools for establishing good cooperation between the three components above. The results of this study state that there are two patterns of social interaction, namely formal and informal interactions. And the role of the family as well as the community for the implementation of moral education in schools is very important.Abstrak. Masyarakat sosial sangat berpengaruh terhadap keberhasilan pendidikan di sekolah. Keduanya saling terkait dan tidak bisa dipisahkan satu dengan lainnya. Kontribusi sosiologi yang dibahas di sini adalah tentang peran keluarga, masyarakat dan sekolah dalam mencapai hasil pendidikan yang diinginkan bagi siswa, yaitu siswa yang berakhlak baik dan berprestasi di sekolahnya. Pendidikan akhlak sendiri menjadi pondasi untuk terbentuknya masyarakat yang baik. Untuk itu perlu di ketahui apa saja pola interaksi yang bisa terjalin di antara ketiga peran tersebut dan apa saja andil keluarga dan masyarakat dalam mendidik akhlak siswa. Penelitian ini bersifat kualitatif, tehnik pengumpulan datanya dilakukan dengan studi pustaka dan objek kajiannya mengenai pelaksanaan pendidikan akhlak di sekolah dan sosiologi yang menjadi alat terjalinnya kerjasama yang baik antara tiga komponen di atas. Hasil dari penelitian ini menyatakan bahwa ada dua pola interaksi sosial, yaitu interaksi formal dan informal. Dan peran keluarga dan masyarakat bagi pelaksanaan pendidikan akhlak sangat penting.